The State of Working America, 1998-99 - Dresser, Laura (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "The State of Working America, 1998-99," by Lawrence Mishel, Jared Bernstein, and John Schmitt.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Business conditions; Economic conditions; Economic indicators; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z